Cyclotide discovery in Gentianales revisited—identification and characterization of cyclic cystine‐knot peptides and their phylogenetic distribution in Rubiaceae plants. Issue 5 (19th September 2013) - Koehbach, Johannes; Attah, Alfred F.; Berger, Andreas; Hellinger, Roland; Kutchan, Toni M.; Carpenter, Eric J.; Rolf, Megan; Sonibare, Mubo A.; Moody, Jones O.; Wong, Gane Ka‐Shu; Dessein, Steven; Greger, Harald; et al.
ABSTRACT Cyclotides are a unique class of ribosomally synthesized cysteine‐rich miniproteins characterized by a head‐to‐tail cyclized backbone and three conserved disulfide‐bonds in a knotted arrangement. Originally they were discovered in the coffee‐family plant Oldenlandia affinis (Rubiaceae) and have since been identified in several species of the violet, cucurbit, pea, potato, and grass families. However, the identification of novel cyclotide‐containing plant species still is a major challenge due to the lack of a rapid and accurate analytical workflow in particular for large sampling numbers. As a consequence, their phylogeny in the plant kingdom remains unclear. To gain further insight into the distribution and evolution of plant cyclotides, we analyzed ∼300 species of >40 different families, with special emphasis on plants from the order Gentianales. For this purpose, we have developed a refined screening methodology combining chemical analysis of plant extracts and bioinformatic analysis of transcript databases. Using mass spectrometry and transcriptome‐mining, we identified nine novel cyclotide‐containing species and their related cyclotide precursor genes in the tribe Palicoureeae. The characterization of novel peptide sequences underlines the high variability and plasticity of the cyclotide framework, and a comparison of novel precursor proteins from Carapichea ipecacuanha illustrated their typical cyclotide gene architectures. Phylogenetic analysis of their distribution within the Psychotria alliance revealed cyclotides to be restricted to Palicourea, Margaritopsis, Notopleura, Carapichea, Chassalia, and Geophila. In line with previous reports, our findings confirm cyclotides to be one of the largest peptide families within the plant kingdom and suggest that their total number may exceed tens of thousands. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 438–452, 2013.